Genome-wide association study identifies five new susceptibility loci for prostate cancer in the Japanese population - Takata, Ryo; Akamatsu, Shusuke; Kubo, Michiaki; Takahashi, Atsushi; Hosono, Naoya; Kawaguchi, Takahisa; Tsunoda, Tatsuhiko; Inazawa, Johji; Kamatani, Naoyuki; Ogawa, Osamu; Fujioka, Tomoaki; Nakamura, Yusuke; et al. (Nature genetics, 2010)
Hidewaki Nakagawa and colleagues report a genome-wide association study for prostate cancer in a Japanese population. They replicate previously associated loci and identify five new susceptibility loci. Prostate cancer is one of the most common malignancies in males throughout the world 1 , and its incidence is increasing in Asian countries. We carried out a genome-wide association study and replication study using 4,584 Japanese men with prostate cancer and 8,801 control subjects. From the thirty-one associated SNPs reported in previous genome-wide association studies in European populations, we confirmed the association of nine SNPs at P < 1.0 × 10 −7 and ten SNPs at P < 0.05 in the Japanese population. The remaining 12 SNPs showed no association ( P > 0.05). In addition, we report here five new loci for prostate cancer susceptibility, at 5p15 (λ-corrected probability P GC = 3.9 × 10 −18 ), GPRC6A/RFX6 ( P GC = 1.6 × 10 −12 ), 13q22 ( P GC = 2.8 × 10 −9 ), C2orf43 ( P GC = 7.5 × 10 −8 ) and FOXP4 ( P GC = 7.6 × 10 −8 ). These findings advance our understanding of the genetic basis of prostate carcinogenesis and also highlight the genetic heterogeneity of prostate cancer susceptibility among different ethnic populations.